CRM as a competitive advantage - Čierna, Helena; Bárdošová, Lucia (Manufacturing Technology Journal, 2013)
In order to increase their own competitiveness, companies have to adapt to market conditions and factors that directly affect them - suppliers, competitors, customers. In particular, at present - in a society of excess, the issue of competitiveness is growing. Enterprises have only a limited amount of resources to serve them as a competitive advantage, and it is essential that they invest as efficiently as possible. The companies can implement this only if there is a full understanding of customer needs and the environment in which they carry out their business. Products are converging by their quality and characteristics, and no one can achieve a competitive advantage only by the physical characteristics of products and prices. To have a successful business, it is vital to be able to identify valuable customers, and build a mutually beneficial relationship with them based on customer satisfaction, loyalty and trust. In this respect, the strategy for Customer Relationship Management (CRM) is being conductive. The strategy is based on individual customer care, identifying their needs and creating mutually beneficial relationships between enterprise and customer and creating value for customers.
Keywords: Customer relationship management; differentiated approach to customers; customer value; competitiveness of companies